Idiomatic Meaning in English Compounds: A Semantic Analysis of Non-Literal Interpretations - Luwiti, Sri Rumiyatiningsih (Reduplikasi: Jurnal Penelitian Pendidikan Bahasa Indonesia, 2024)
Idiomatic compounds in English often present challenges for learners, particularly those for whom English is a second language (ESL). These compounds, such as "brainstorm" and "blackmail," exhibit meanings that deviate from their literal components, leading to confusion in interpretation. This study investigates the processes involved in the semantic shift from literal to idiomatic meanings in English compounds. Using a qualitative approach, idiomatic compounds are analyzed through a semantic lens, identifying the cultural and metaphorical influences that shape their meanings. This study shows that English compound words undergo semantic shifts, with compositional compounds (e.g., "honeymoon") retaining some literal meaning, while non-compositional compounds (e.g., "blackmail") obscure the original meanings entirely. The findings illustrate how metaphor and culture influence the development of idiomatic expressions in language.Â